Rapidly improving acute respiratory distress syndrome in COVID-19: a multi-centre observational study - Evdokia Gavrielatou; Katerina Vaporidi; Vasiliki Tsolaki; Nikos Tserlikakis; George E. Zakynthinos; Eleni Papoutsi; Aikaterini Maragkuti; Athina G. Mantelou; Dimitrios Karayiannis; Zafeiria Mastora; Dimitris Georgopoulos; Epaminondas Zakynthinos; et al. (Respiratory Research, 2022)
Abstract Background Before the pandemic of coronavirus disease (COVID-19), rapidly improving acute respiratory distress syndrome (ARDS), mostly defined by early extubation, had been recognized as an increasingly prevalent subphenotype (making up 15–24% of all ARDS cases), associated with good prognosis (10% mortality in ARDSNet trials). We attempted to determine the prevalence and prognosis of rapidly improving ARDS and of persistent severe ARDS related to COVID-19. Methods We included consecutive patients with COVID-19 receiving invasive mechanical ventilation in three intensive care units (ICU) during the second pandemic wave in Greece. We defined rapidly improving ARDS as extubation or a partial pressure of arterial oxygen to fraction of inspired oxygen ratio (PaO2:FiO2) greater than 300 on the first day following intubation. We defined persistent severe ARDS as PaO2:FiO2 of equal to or less than 100 on the second day following intubation. Results A total of 280 intubated patients met criteria of ARDS with a median PaO2:FiO2 of 125.0 (interquartile range 93.0–161.0) on day of intubation, and overall ICU-mortality of 52.5% (ranging from 24.3 to 66.9% across the three participating sites). Prevalence of rapidly improving ARDS was 3.9% (11 of 280 patients); no extubation occurred on the first day following intubation. ICU-mortality of patients with rapidly improving ARDS was 54.5%. This low prevalence and high mortality rate of rapidly improving ARDS were consistent across participating sites. Prevalence of persistent severe ARDS was 12.1% and corresponding mortality was 82.4%. Conclusions Rapidly improving ARDS was not prevalent and was not associated with good prognosis among patients with COVID-19. This is starkly different from what has been previously reported for patients with ARDS not related to COVID-19. Our results on both rapidly improving ARDS and persistent severe ARDS may contribute to our understanding of trajectory of ARDS and its association with prognosis in patients with COVID-19.